2008
DOI: 10.1186/1745-6673-3-32
|View full text |Cite
|
Sign up to set email alerts
|

Burnout: need help?

Abstract: Background: Burnout syndrome is a psychological situation induced with working, especially in high-risk parts of the hospitals that affects the physical and mental conditions of the staff. The aim is to identify the characteristics of the staff related to Burnout Syndrome in the Emergency Department (ED).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 8 publications
0
16
0
3
Order By: Relevance
“…In the US, around 9% of 8000 surgeons reported that they made medical errors. Burnout has been found associated with substance abuse, lack of motivation, and performance, which can lead to medical errors [6,7]. There are many factors for job dissatisfaction among inpatient nurses such as dealing with death cases and a stressful work environment [8].…”
Section: Introductionmentioning
confidence: 99%
“…In the US, around 9% of 8000 surgeons reported that they made medical errors. Burnout has been found associated with substance abuse, lack of motivation, and performance, which can lead to medical errors [6,7]. There are many factors for job dissatisfaction among inpatient nurses such as dealing with death cases and a stressful work environment [8].…”
Section: Introductionmentioning
confidence: 99%
“…Nursing is a stressful profession that deals with human aspects of health and illness [1][2][3], and can ultimately lead to job dissatisfaction and burnout Burnout is a mental condition defined as the body's response to the failure of the coping strategies that individuals typically utilize to manage stress at work [4][5][6]. The accumulation of stress exhausts individuals to the point where their energy resources are insufficient for their attempts to overcome the pressure of a situation in which they work with other people [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…According to Gülalp, Karcıoğlu, Sarı & Köseoğlu (2008) there is lack of adequate linkage between marital status and burnout. By contrast, Ifeagwazi (2006) claims that married employees' burnout levels are significantly lower than single employees' burnout levels.…”
Section: Emotional Exhaustionmentioning
confidence: 99%
“…According to Dillon & Tanner (1995) and more recently Yıldırım (2008) it might be said that gender, age and marital status have not linkage with burnout. However, in contrast to these researchers Jackson (1993) and Cordes & Dougherty (1993) claim that there is a plausible link between these variables.According to Gülalp, Karcıoğlu, Sarı & Köseoğlu (2008) there is lack of adequate linkage between marital status and burnout. By contrast, Ifeagwazi (2006) claims that married employees' burnout levels are significantly lower than single employees' burnout levels.…”
mentioning
confidence: 99%